Critical limb-threatening ischaemia and microvascular transformation: clinical implications - Tarvainen Santeri; Wirth Galina; Juusola Greta; Hautero Olli; Kalliokoski Kari; Sjöros Tanja; Nikulainen Veikko; Taavitsainen Jouni; Hytönen Jarkko; Frimodig Crister; Happonen Krista; Selander Tuomas; et al. (Oxford University Press, 2025)
Background and Aims
Clinical management of critical limb-threatening ischaemia (CLTI) is focused on prevention and treatment of atherosclerotic arterial occlusions. The role of microvascular pathology in disease progression is still largely unspecified and more importantly not utilized for treatment. The aim of this explorative study was to characterize the role of the microvasculature in CLTI pathology.
Methods
Clinical high-resolution imaging of CLTI patients (n = 50) and muscle samples from amputated CLTI limbs (n = 40) were used to describe microvascular pathology of CLTI at the level of resting muscle blood flow and microvascular structure, respectively. Furthermore, a chronic, low arterial driving pressure-simulating ischaemia model in rabbits (n = 24) was used together with adenoviral vascular endothelial growth factor A gene transfers to study the effect of microvascular alterations on muscle outcome.
Results
Resting microvascular blood flow was not depleted but displayed decreased capillary transit time (P < .01) in CLTI muscles. Critical limb-threatening ischaemia muscle microvasculature also exhibited capillary enlargement (P < .001) and further arterialization along worsening of myofibre atrophy and detaching of capillaries from myofibres. Furthermore, CLTI-like capillary transformation was shown to worsen calf muscle force production (P < .05) and tissue outcome (P < .01) under chronic ischaemia in rabbits and in healthy, normal rabbit muscle.
Conclusions
These findings depict a progressive, hypoxia-driven transformation of the microvasculature in CLTI muscles, which pathologically alters blood flow dynamics and aggravates tissue damage under low arterial driving pressure. Hypoxia-driven capillary enlargement can be highly important for CLTI outcomes and should therefore be considered in further development of diagnostics and treatment of CLTI.